Dexmedetomidine Protects Against Septic Liver Injury by Enhancing Autophagy Through Activation of the AMPK/SIRT1 Signaling Pathway - Yu, Qing; Zou, Liying; Yuan, Xiu; Fang, Fang; Xu, Feng (Frontiers in Pharmacology, 2021)
Liver injury is one of the serious complications of sepsis. Previous studies suggested that dexmedetomidine (DEX) could alleviate cecal ligation and puncture (CLP)-induced liver injury. However, it is unclear whether the protective effect of DEX on sepsis-induced liver injury is related to autophagy. Mice (n = 105) mice were randomly divided into the following groups: (i) CON group (Sham); (ii) CLP group (CLP-induced liver injury + saline); (iii) CLP + DEX group (CLP induced liver injury + DEX). Mouse models of sepsis-induced liver injury were established using CLP. DEX or normal saline was administered by intraperitoneal injection at 0, 2 and 4 h after CLP surgery. The mortality rate within 120 hours was calculated. The levels of alanine aminotransferase (ALT), aspartate aminotransferase (AST), and inflammatory cytokines were measured at 6, 12, and 24 h in each group. Hematoxylin and eosin staining assay was carried out to detect the morphological changes of mouse liver cells in each group. The levels of autophagy-associated proteins LC3II, Beclin-1, p62, and LAMP-2 were detected in three groups of mice using western blotting. The expression of LC3II was detected using immunofluorescence. Transmission electron microscopy (TEM) of liver tissue was used to observe autophagosomes and autophagosome–lysosomes. Lastly, the effect of DEX on the AMPK/SIRT1 pathway-associated protein levels were detected using western blotting. DEX significantly improved the survival rate of septic mice at the early stage and ameliorated the pathology of sepsis-induced liver injury. The level of autophagy-associated proteins, phosphorylated (p)-AMPK/AMPK, and SIRT1 in the liver of CLP-induced sepsis mice peaked at 12 h post-CLP and decreased significantly at 24 h. In the CLP + DEX group, the levels of autophagy-associated proteins, p-AMPK/AMPK, and SIRT1 increased, whereas inflammatory cytokines decreased at 24 h. The autophagosome structure was clearly observed at different time points in the CLP + DEX group. We demonstrated a novel mechanism in which DEX protects against CLP-induced liver injury. DEX enhances autophagy, which alleviates the inflammatory responses in CLP induced liver injury by regulating the SIRT1/AMPK pathway.